The Organic Roots of Conatus in Early Greek Thought - Kirby, Christopher (Conatus - Journal of Philosophy, 2021)
The focus of this paper will be on the earliest Greek treatments of impulse, motivation, and self-animation – a cluster of concepts tied to the hormē-conatus concept. I hope to offer a plausible account of how the earliest recorded views on this subject in mythological, pre-Socratic, and Classical writings might have inspired later philosophical developments by establishing the foundations for an organic, wholly naturalized approach to human inquiry. Three pillars of that approach which I wish to emphasize are: practical intelligence (i.e., a continuity between knowing and doing), natural normativity (i.e., a continuity between human norms and the environment), and an ontology of philosophical dialectic (i.e., a continuity between the growth of human understanding and the growth of physis).